Advancing the concept of consumption corridors and exploring its implications. Issue 1 (1st January 2021) - Sahakian, Marlyne; Fuchs, Doris; Lorek, Sylvia; Di Giulio, Antonietta
Abstract: As a salutogenic concept, "consumption corridors" aims to support what is necessary for sustainable wellbeing to be achieved in relation to the Earth system, with a deep consideration for justice and equity. Living in consumption corridors is a representation of everyday life whereby people live within limits, so that all people – now and in the future – can access what is needed to live a good life. In this special issue, a series of scholars and practitioners have come together to further develop the concept, engage with its methodological implications, and relate it to consumption domains and policy implications. We begin by introducing how the concept emerged, in relation to the complexity of grappling with the societal transformations required for achieving more sustainable forms of consumption. We then present the different contributions, which demonstrate the importance of considering both maximum and minimum consumption standards, the relevance of human-need theories, as well as the difference between achieving wellbeing and the means necessary for doing so. We conclude by opening up to areas that merit further deliberation: how to relate consumption corridors to everyday-life dynamics, but also to the critical question of power relations at play in implementing consumption corridors.